Neuroimaging Studies of Chronic Prostatitis/Chronic Pelvic Pain Syndrome - Yifan Zhao; Jiaqi Lin; Ye Dong; Zilei Tian; Yan Ye; Ziyang Ma; Shengli Xia; Xiaopeng Huang; Diang Chen; Peihai Zhang (Pain Research and Management)
Evidence shows that chronic prostatitis/chronic pelvic pain syndrome hugely impacts the body and mind. The central mechanisms in patients with CP/CPPS resulted in increased attention as neuroimaging techniques developed. This review investigated the study design and major neuroimaging findings in CP/CPPS patients to provide comprehensive evidence. Seven databases were searched and screened: PubMed, EMBASE/SCOPUS, Cochrane Library Database, China National Knowledge Infrastructure, VIP, Wanfang, and China Biology Medicine disc. Nine studies were eventually included in the analysis. The results demonstrate that the insula, anterior cingulate gyrus, postcentral gyrus, and precuneus are significantly associated with CP/CPPS patients’ pain feelings and cause dysregulation of painful emotions, lowering patients’ tolerance to stimulus.